RISK MANAGEMENT IN SANATORIUM ACTIVITIES - Hanynets, P. P. (Medical Informatics and Engineering, 2017)
The methodology of evaluation of functioning of the sanatorium activity management system is proposed. Management risks are justified. For the management quality assessment system, the dual control principle is applied, which allowed to replace the multidimensional model of institution management by a two-level model that to some extent harmonizes the existing system of criteria and indicators. At the first level (managed system) there are criteria, indicators and characteristics of technological processes in the sanatorium. At the second level (management system) there are integrated models, criteria and performance indicators of management structures and operations of the sanatorium.